Beyond the Limit in Piranesi’s Art (diségno, 2021)
The contribution investigates the theme of overcoming the limit in Piranesi’s art, examining the subject in three different aspects: the technical, perspective and architectural fields.In the technical sphere, Piranesi went beyond the limit during his incessant experimentation to get the secret of etching to which he aspired. The price he had to pay to achieve the freedom, poetry and freshness of sign, with which he expressed the power, depth and audacity of his imagination, concerned some technical failures found on the copper matrices.His overcoming the limits in the field of perspective is demonstrated by the expedients with which Piranesi skilfully mastered perspective to adapt the composition to his aesthetic and expressive wishes, anticipating and synthesising modern cinematographic techniques in a single image.In architecture, the overcoming of limits can be found in his inventions: in the impossible configurations of the Carceri and the colossal architectural fantasies collected in the Opere varie. Not having the opportunity to devote himself to concrete design practice, Piranesi entrusted his utopias to imagination and drawing.
Keywords: Piranesi; limit; etching; perspective; architectural fantasies